2013
DOI: 10.1080/00220388.2012.754432
|View full text |Cite
|
Sign up to set email alerts
|

The Pedagogy of Science and Environment: Experimental Evidence from Peru

Abstract: In today's knowledge-based societies, understanding basic scientific concepts and the capacity to structure and solve scientific questions is more critical than ever. Accordingly, in this paper we test an innovative methodology for teaching science and environment in public primary schools where traditional (teacher centred) teaching was replaced with student centred activities using LEGO kits. We document positive and significant improvements of 0.18 standard deviations in standardised test scores. Such posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…Initiatives aimed at influencing parental practices have been more effective in improving the developmental and academic skills of children during their first few years of life. 73 Similarly, Beuermann, Naslund-Hadley, Ruprah, & Thompson (2013) assessed a program that aimed to teach science in third grade in Lima, Peru in 2010 in which the teacher posed a problem, provided the materials to solve it, and students had to conduct their own experiments and report their results. The program improved test scores on the physical world assessment by .18 SDs, but not scores on assessments of understanding of the human body and the environment.…”
Section: Discussionmentioning
confidence: 99%
“…Initiatives aimed at influencing parental practices have been more effective in improving the developmental and academic skills of children during their first few years of life. 73 Similarly, Beuermann, Naslund-Hadley, Ruprah, & Thompson (2013) assessed a program that aimed to teach science in third grade in Lima, Peru in 2010 in which the teacher posed a problem, provided the materials to solve it, and students had to conduct their own experiments and report their results. The program improved test scores on the physical world assessment by .18 SDs, but not scores on assessments of understanding of the human body and the environment.…”
Section: Discussionmentioning
confidence: 99%
“…The default government training in the control group represents the public status quo, making the comparison with treatment highly relevant for policy. 8 The outreach component builds on studies of other training programs with similar follow-up for trained teachers (e.g., Beuermann et al 2013;Abeberese, Kumler, and Linden 2014;Piper and Zuilkowski 2015). The exchange visits resemble a form of teacher coaching (e.g., Bruns, Costa, and Cunha 2018;Albornoz et al 2018;Cilliers et al 2019), except that trained teachers received feedback from peers rather than professional coaches.…”
Section: Methodsmentioning
confidence: 99%
“…Consistent with the idea of many students falling behind the national curriculum, a randomized evaluation concluded that the 2010 pilot program only improved the achievement of third-grade students who already had above-average baseline performances (Beuermann, et al 2013). 1 Remedial education, by which students receive targeted, self-paced teaching, shows promise at improving short-and medium-term academic performance of low-achieving students in a variety of contexts.…”
Section: Introductionmentioning
confidence: 95%